A water-stable pyridine bisphosphonate-based metal–organic framework as a selective and sensitive luminescent probe for Cr(VI) ions and acetone. Issue 7 (30th April 2021) - Duan, Shao-Long; Zou, Wen-Kang; Guan, Yu; Lu, Zhi-Wei; Hu, Ming-Han; Wu, Yu-Fei; Li, Yu-Qing; Zhang, Hui; Zou, Ping; Wang, Guang-Tu
Abstract: A rare photoluminescent nitroxide pyridine bisphosphonate-based metal– organic framework, [Eu4 (L)3 (H2 O)6 ]n (1 ) [H4 L = 2, 6-bis(phosphonomethyl)pyridine 1-oxide], was prepared under hydrothermal conditions and has a 3D supramolecular structure built from phosphonate linkers bridging Eu 3+ . It was characterized by single-crystal X-ray diffraction (SXRD), powder X-ray diffraction (PXRD), thermogravimetric analyses (TGAs), etc . The luminescence spectra of 1 show the strong characteristic luminescence of Eu 3+ ions, and 1 shows high water stability, thermal stability, and chemical stability. Furthermore, luminescence studies have shown that 1 can be used as a fluorescent probe for detecting trace amounts of Cr(VI) ions and acetone in water samples with excellent sensitivity, great selectivity, and reproducibility. The detection limits are as low as 0.61 μM, 0.63 μM, and 0.0066 vol% for Cr2 O7 2-, CrO4 2-, and acetone, respectively. The fluorescence quenching of 1 by Cr(VI) ions and acetone may be due to spectral overlap and absorption competition. This is the first example of a Eu-based pyridine phosphonate fluorescence sensor for simultaneous detection of Cr(VI) ions and acetone. Graphical Abstract: